The Role of Lecturers in Society 5.0 for Advancing Indonesia - Umi Zulfa; M. Hanif; Ismah (Innovation Business Management and Accounting Journal, 2025)
Society 5.0, a Japanese concept aiming to integrate physical and digital worlds to enhance human quality of life, contrasts with Industry 4.0's focus on industrial automation. In Indonesia, this paradigm shift underscores the pivotal role of education, particularly the role of lecturers, in preparing a generation capable of adapting to and advancing in this era. This paper explores the strategic role of lecturers in fostering superior human resources for an advanced Indonesia in the Society 5.0 context. It employs qualitative library research and content analysis to examine the role of lecturers as educators, innovators, researchers, and career mentors. Key aspects include integrating technology into teaching, creating relevant curricula, conducting impactful research, and preparing students for global challenges. Despite facing challenges such as limited access to technology and inadequate training, lecturers are essential in leveraging technological advancements to produce adaptable, competent graduates. The paper concludes that addressing these challenges through infrastructure investment and continuous professional development is crucial for Indonesia to thrive in the Society 5.0 era.